Vapour pressures and osmotic coefficients of binary mixtures containing alcohol and pyrrolidinium-based ionic liquids - N. Calvar (2013)
The osmotic and activity coefficients and vapour pressures of mixtures containing primary (1-propanol, 1-butanol and 1-pentanol) and secondary (2-propanol and 2-butanol) alcohols with pyrrolidinium-based ionic liquids (1-butyl-1-methyl pyrrolidinium bis(trifluoromethylsulfonyl)imide, C(4)MpyrNTf(2), and 1-butyl-1-methyl pyrrolidinium trifluoromethanesulfonate, C(4)MpyrTFO) have been experimentally determined at T = 323.15 K. For the experimental measurements, the vapour pressure osmometry technique has been used. The results on the influence of the structure of the alcohol and of the anion of the ionic liquid on the determined properties have been discussed and compared with literature data. For the correlation of the osmotic coefficients obtained, the Extended Pitzer model of Archer and the Modified Non-Random Two Liquids model were applied. The mean molal activity coefficients and the excess Gibbs energy for the studied mixtures were calculated from the parameters obtained in the correlation.